Development of an E-module on the Material of Substance Pressure and Its Use in Daily Life, Based on Science Process Skills - Fitriyah, Isnanik Juni; Andik, Andik Wahyun Muqoyyidin; Septi, Septi Aprilia (Universitas Islam Indonesia, 2025)
The science learning process is anticipated to be able to offer an independent learning experience by utilizing previously acquired skills, namely science process skills. Based on the needs analysis, students get bored easily, are lazy, and find it difficult to accept science learning. In addition, worksheets and printed books that are used as learning resources have not implemented current technological developments, as a result students are bored and less interested. Teachers as science learning practitioners still find it difficult to provide learning media that have the capacity to pique students' interest. So, this research was conducted to develop an e-module centered on scientific process skills in the area of substance stress and its practical application, as well as evaluating its efficacy. The methodology employed in the research was the ADDIE R&D model which was carried out in class IX at SMP Nasional Malang. Data collection was done through student analysis questionnaires, media validity questionnaires, material validity questionnaires, student readability test questionnaires, and practicality test questionnaires by science teachers. Overall, the validity of the material is 92%, the validity of the media is 97.2%, the readability of students is 86.61%, and the practicality of science teachers is 99%. Therefore, this e-module is very feasible and effective to be applied to the science learning process in junior high schools on substance stress and its application in daily life.